Inter Relationship of Teacher Self-Esteem in Private Secondary Schools of Lahore - Anwar, Muhammad; Nasreen, Shariqa (Annals of Human and Social Sciences, 2024)
Teachers play a pivotal role in nation-building, and secondary school educators in Pakistan are vital to social and academic development. This is particularly true in the private sector, which employs over a million teachers. A study focused on self-esteem, professional commitment, and intra-professional diversity among private secondary school teachers in Lahore, Punjab, aimed to provide insights for policymakers. Both high- and low-paying private secondary schools in Lahore, accredited by the Board of Intermediate and Secondary Education, were included in the study. Random sampling was used to select participants, resulting in data. The study employed a mixed-methods approach, gathering quantitative and qualitative data through modified surveys and teacher interviews. The findings indicate that higher self-esteem among teachers correlates with more tremendous occupational success and professional commitment. Enhancing self-esteem can, therefore, increase job dedication and career achievement. The study also highlights that teacher self-esteem and intra-professional diversity significantly impact teaching and learning positively and negatively. These insights are crucial for developing policies that support teacher development and improve educational outcomes.